2018
DOI: 10.1109/lawp.2018.2848723
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Modulated Triple-Ridge Leaky-Wave Antenna

Abstract: This article investigates the potential of additive manufacturing for the fabrication of complex antenna geometries with enhanced performance at K-band. Stereolithography is here used to 3D-print a novel topology of dual-polarized leaky-wave antenna that allows for the control of its aperture illumination both in phase and magnitude. The antenna consists of a modulated triple-ridge square waveguide perforated on its top wall with crossed slots of different sizes. An orthomodetransducer is integrated within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The LWA has been monolithically manufactured using a metal Additive Manufacturing (AM) process based on Selective Laser Melting (SLM) combined with metal plating. Previous work by these authors considered a different technique based on polymer 3D-printing [8], [9]. To their best knowledge, this is the first proof of successful SLM prototyping of a leaky-waveguide.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The LWA has been monolithically manufactured using a metal Additive Manufacturing (AM) process based on Selective Laser Melting (SLM) combined with metal plating. Previous work by these authors considered a different technique based on polymer 3D-printing [8], [9]. To their best knowledge, this is the first proof of successful SLM prototyping of a leaky-waveguide.…”
Section: Introductionmentioning
confidence: 92%
“…The two arms in a cross may be of . different length, and their dimensions may vary along the y-axis [8]. The LWA is fed through a WR42 waveguide.…”
Section: Dual-mode Lwa: Structure and Dispersion Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, additive manufacturing (AM) has revolutionized both the commercial and research industries by presenting different kinds of rapid prototyping techniques for realizing complex geometries and structures. Particularly, multiple research groups have reported various additive manufacturing methods for prototyping antennas such as triple-ridge leaky-wave antennas, quad-ridged horn antennas, ring-focus dual-reflector antennas, and dual-polarized leaky-wave antennas [25][26][27][28][29]. The inkjet printing technology of additive manufacturing was also adopted to develop conformal microstrip antennas using a piezoelectric nozzle array [30], a patch antenna emitter for wireless communication [31], and a 3D patch antenna with integrated polymer and metal [32].…”
Section: Introductionmentioning
confidence: 99%
“…Possible designs synthesizing such a line source may rely on dual-polarized slotted waveguide arrays [7], [8]. As an alternative, the dual-polarized array could be excited by a dual-mode quasi-optical system, e.g.…”
Section: Introductionmentioning
confidence: 99%